Vibrational control of selective bond cleavage in dissociative chemisorption of methanol on Cu(111) - Jialu Chen (Nature Portfolio, 2018)
Dissociative chemisorption of methanol on metal surfaces is a key step for hydrogen production. Here the authors use quasi-quantized molecular dynamics simulations to alter the branching ratios for methanol dissociative chemisorption on Cu(111) via selectively exciting specific vibrational modes.